2022
DOI: 10.1155/2022/2498435
|View full text |Cite|
|
Sign up to set email alerts
|

C-Reactive Protein, Procalcitonin, and a Novel Pathogenesis and Therapeutic Target of Thrombocytopenia in Sepsis

Abstract: Objective. The aim of the study is to analyze the clinical characteristics, pathogen distribution, and drug sensitivity information of adult sepsis, and to provide reference for empirical clinical use; to explore the relationship between C-reactive protein (CRP) and calcitonin (PCT) The clinical value in the diagnosis of adult sepsis. Methods. We collected 455 cases of hospitalized patients with positive blood culture, including 352 cases with sepsis and 103 cases without sepsis; 1609 cases of hospitalized pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…It was originally found in the blood of patients infected with streptococcus pneumoniae. 28 CRP concentrations began to rise 6 h after bacterial infection and reached a maximum after 24–48 h. 29 It is reported that CRP is often elevated in AP patients and helps to assess the severity of the disease. 30 Consistently, significantly elevated levels of CRP were detected SAP patients compared with non‐severe cases, indicating the diagnostic potential of CRP in SAP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was originally found in the blood of patients infected with streptococcus pneumoniae. 28 CRP concentrations began to rise 6 h after bacterial infection and reached a maximum after 24–48 h. 29 It is reported that CRP is often elevated in AP patients and helps to assess the severity of the disease. 30 Consistently, significantly elevated levels of CRP were detected SAP patients compared with non‐severe cases, indicating the diagnostic potential of CRP in SAP.…”
Section: Discussionmentioning
confidence: 99%
“…It was originally found in the blood of patients infected with streptococcus pneumoniae 28 . CRP concentrations began to rise 6 h after bacterial infection and reached a maximum after 24–48 h 29 . It is reported that CRP is often elevated in AP patients and helps to assess the severity of the disease 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%